Endogenous morphine‐6‐glucuronide (M6G) is present in the plasma of patients: Validation of a specific anti‐M6G antibody for clinical and basic research. (17th July 2013) - Laux‐Biehlmann, Alexis; Chung, Hélène; Mouheiche, Jinane; Vérièpe, Julie; Delalande, François; Lamshöft, Marc; Welters, Ingeborg D.; Soldevila, Stéphanie; Bazin, Hervé; Lamarque, Laurent; Dorsselaer, Alain Van; Poisbeau, Pierrick; et al.
<x xml:space="preserve">Abstract</x> Endogenous morphine and its derivatives (morphine‐6‐glucuronide [M6G]; morphine‐3‐glucuronide [M3G]) are formed by mammalian cells from dopamine. Changes in the concentrations of endogenous morphine have been demonstrated in several pathologies (sepsis, Parkinson's disease, etc.), and they might be relevant as pathological markers. While endogenous morphine levels are detectable using enzyme‐linked immunosorbant assay (ELISA), mass spectrometry (MS) analysis was, so far, the only approach to detect and quantify M6G. This study describes the preparation of a specific anti‐M6G rabbit polyclonal antibody and its validation. The specificity of this antibody was assessed against 30 morphine‐related compounds. Then, a M6G‐specific ELISA‐assay was tested to quantify M6G in the plasma of healthy donors, morphine‐treated, and critically ill patients. The antibody raised against M6G displays a strong affinity for M6G, codeine‐6‐glucuronide, and morphine‐3‐6‐glucuronide, whereas only weak cross‐reactivities were observed for the other compounds. Both M6G‐ELISA and LC‐MS/MS approaches revealed the absence of M6G in the plasma of healthy donors (controls, n = 8). In all positive donors treated with morphine‐patch (n = 5), M6G was detected using both M6G‐ELISA and LC‐MS/MS analysis. Finally, in a study on critically ill patients with circulating endogenous morphine (n = 26), LC‐MS/MS analysis revealed that 73% of the positive‐patients (19 of 26), corresponding to high M6G‐levels in M6G‐ELISA, contained M6G. In conclusion, we show that endogenous M6G can be found at higher levels than morphine in the blood of morphine‐naive patients. With respect to the interest of measuring endogenous M6G in pathologies, we provide evidences that our ELISA procedure represents a powerful tool as it can easily and specifically detect endogenous M6G levels. © 2013 BioFactors, 40(1):113–120, 2014